Texts from the Swedish Pension Authority - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Parallel texts in form of (orange) reports from the website of the Swedish Pension Authority.

Parallel texts downloaded from the website of the Swedish Pension Authority. What was actually downloaded were pdf files. The txt files that are available are the result of running the pdf files through the pdftotext command from an ubuntu shell.

Parallella texter i form av rapporter (Orange rapport) från Pensionmyndighetens webbplats.

Parallella texter nedladdade från Pensionsmyndighetens webbplats. Det som nedladdades var egentligen pdf-filer. Det som finns tillgängligt är txt-filer som resulterat ur en körning av kommandot pdftotext i ubuntu-skal.
Texter från Pensionsmyndigheten
Keywords: public administration; offentlig förvaltning; Retirement; Pension; SOCIAL WELFARE POLICY AND SYSTEMS; SOCIAL VÄLFÄRDSPOLITIK OCH VÄLFÄRDSSYSTEM; Social Sciences; Samhällsvetenskap; Economics; Nationalekonomi; Languages and Literature; Språk och litteratur; Public Administration Studies; Studier av offentlig förvaltning